Emodin Induces Apoptotic Death in Murine Myelomonocytic Leukemia WEHI-3 Cells In Vitro and Enhances Phagocytosis in Leukemia Mice In Vivo. (10th May 2011) - Chang, Yuan-Chang; Lai, Tung-Yuan; Yu, Chun-Shu; Chen, Hung-Yi; Yang, Jai-Sing; Chueh, Fu-Shin; Lu, Chi-Cheng; Chiang, Jo-Hua; Huang, Wen-Wen; Ma, Chia-Yu; Chung, Jing-Gung
Abstract : Emodin is one of major compounds in rhubarb ( Rheum palmatum L.), a plant used as herbal medicine in Chinese population. Although many reports have shown that emodin exhibits anticancer activity in many tumor cell types, there is no available information addressing emodin-affected apoptotic responses in the murine leukemia cell line (WEHI-3) and modulation of the immune response in leukemia mice. We investigated that emodin induced cytotoxic effects in vitro and affected WEHI-3 cells in vivo . This study showed that emodin decreased viability and induced DNA fragmentation in WEHI-3 cells. Cells after exposure to emodin for 24 h have shown chromatin condensation and DNA damage. Emodin stimulated the productions of ROS and Ca 2+ and reduced the level of Δ Ψ m by flow cytometry. Our results from Western blotting suggest that emodin triggered apoptosis of WEHI-3 cells through the endoplasmic reticulum (ER) stress, caspase cascade-dependent and -independent mitochondrial pathways. In in vivo study, emodin enhanced the levels of B cells and monocytes, and it also reduced the weights of liver and spleen compared with leukemia mice. Emodin promoted phagocytic activity by monocytes and macrophages in comparison to the leukemia mice group. In conclusions, emodin induced apoptotic death in murine leukemia WEHI-3 cells and enhanced phagocytosis in the leukemia animal model.